Enhanced anticorrosion performance of copper by novel N-doped carbon dots. (December 2019) - Qiang, Yujie; Zhang, Shengtao; Zhao, Haichao; Tan, Bochuan; Wang, Liping
Graphical abstract: Highlights: NCDs effectively suppress copper corrosion in aggressive acid medium. NCDs can be designated as a modest cathodic-type inhibitor. The NCDs–adsorption film involves both physisorption and chemisorption. Abstract: Researchers recent reported that N-doped carbon dots (NCDs) effectively inhibit steel corrosion in HCl solution, whereas the action mechanism is still uncertain to date. Herein, novel NCDs have been prepared using a facile hydrothermal method. Combining electrochemical, weight loss, and micromorphology techniques, the resultant NCDs were found to effectively suppress copper corrosion in aggressive H2 SO4 medium. NCDs–adsorption film was formed on copper substrate as a barrier that could prevent transportation of corrosive particles. The relevant anticorrosion mechanism of NCDs was proposed in detail, which could provide powerful guidance to design and synthesis new nanomaterials for metal protection from corrosion.